(untitled) (The International Journal for Scientific Research, 2025)
Respirators and artificial lungs are vital tools in the healthcare field, used to support patients suffering from critical respiratory conditions. This research is based on the use of Euler’s equations to understand and analyze the dynamics of airflow in these devices. We will explore the role of Euler’s equations in improving the design of respirators, along with medical examples that illustrate how these equations impact treatment outcomes.